The diagnostic assessment of platelet function defects: part 2: update on platelet disorders - Althaus, Karina; Hoepner, Gero; Zieger, Barbara; Prüller, Florian; Pavlova, Anna; Boeckelmann, Doris; Birschmann, Ingvild; Müller, Jens; Rühl, Heiko; Sachs, Ulrich; Kehrel, Beate; Streif, Werner; et al. (Hämostaseologie, 2025)
Congenital platelet disorders are rare and targeted treatment is usually not possible. Inherited platelet function disorders (iPFDs) can affect surface receptors and multiple platelet responses such as defects of platelet granules, signal transduction, and procoagulant activity. If iPFDs are also associated with a reduced platelet count (thrombocytopenia), it is not uncommon to be misdiagnosed as immune thrombocytopenia. Because the bleeding tendency of the different platelet disorders is variable, a correct diagnosis of the platelet defect based on phenotyping, function analysis, and genotyping is essential, especially in the perioperative setting. In the case of a platelet receptor deficiency, such as Bernard-Soulier syndrome or Glanzmann thrombasthenia, not only the bleeding tendency but also the risk of isoimmunization after platelet transfusions or pregnancy has to be considered. Platelet granule disorders are commonly associated with either intrinsically quantitative or qualitative granule defects due to impaired granulopoiesis, or granule release defects, which can also affect additional signaling pathways. Functional platelet defects require expertise in the clinical bleeding tendency in terms of the disorder when using antiplatelet agents or other medications that affect platelet function. Platelet defects associated with hematological-oncological diseases require comprehensive information about the patient including the clinical implication of the genetic testing. This review focuses on genetics, clinical presentation, and laboratory platelet function analysis of iPFDs with or without reduced platelet number. As platelet defects affecting the cytoskeleton usually show thrombocytopenia, but less impaired or normal platelet functional responses, they are not specifically addressed.
Gesehen am 22.10.2025